Introducing DOE in manufacturing through Taguchi Method Application - Mohd Zahiruddin, Md. Zain; Azuwir, Mohd Nor (Malaysia-Japan University Center (MJUC), 2011)
Malaysia-Japan International Symposium on Advanced Technology (MJISAT 2007) organized by Malaysia-Japan University Center (MJUC), 12th - 15th November 2007 at Kuala Lumpur, Malaysia.